Chemical Proteomic Analysis of Serine Hydrolase Activity in Niemann-Pick Type C Mouse Brain - van Rooden, Eva J.; van Esbroeck, Annelot C. M.; Baggelaar, Marc P.; Deng, Hui; Florea, Bogdan I.; Marques, André R. A.; Ottenhoff, Roelof; Boot, Rolf G.; Overkleeft, Herman S.; Aerts, Johannes M. F. G.; van der Stelt, Mario (Frontiers in Neuroscience, 2018)
The endocannabinoid system is considered to be an endogenous protective system in various neurodegenerative diseases. Niemann-Pick Type C is a neurodegenerative disease in which the role of the endocannabinoid system has not been studied yet. Most of the endocannabinoid enzymes are serine hydrolases, which can be studied using activity-based protein profiling. Here, we report the serine hydrolase activity in brain proteomes of a Niemann-Pick type C mouse model as measured by activity-based protein profiling. Two activity-based protein profiling methods are used: a gel-based method and a chemical proteomics method. The activities of the following endocannabinoid enzymes were quantified: Diacylglycerol diacylglycerol lipase α, α/β-hydrolase domain-containing protein 4 (ABHD4), ABHD6, ABHD12, fatty acid amide hydrolase and monoacylglycerol lipase activities were quantified. Using the gel-based method, two bands were observed for diacylglycerol lipase α. Only the upper band corresponding to this enzyme was significantly decreased in the Niemann-Pick type C mouse model. Chemical proteomics showed that three lysosomal serine hydrolase activities (retinoid-inducible serine carboxypeptidase, cathepsin A and palmitoyl-protein thioesterase 1) were increased in Niemann-Pick C1 protein (NPC1) knockout mouse brain compared to wild type brain, whereas no difference in endocannabinoid hydrolase activity was observed. We conclude that these targets might be interesting therapeutic targets for future validation studies.